Opportunities for sustainable mobility promotion among students of the University of Maribor, Faculty of Organizational Sciences - Senegacnik, Marjan; Baggia, Alenka; Kovacic, Branka Jarc; Vovk, Maryna; Cherednichenko, Olga (University of Maribor, Slovenia, 2020)
The aim of sustainable mobility is to choose means of transport that have the least possible impact on the environment. Since all motor vehicles cause a direct or indirect form of pollution, walking and cycling are an ideal form of mobility from an environmental point of view. If the use of vehicles is taken into account, public transport generates much less pollution per passenger than the car. In addition to logistical problems such as congestion and lack of parking space, the massive use of cars is a major contributory factor to a sharp deterioration in air quality in urban areas and causes emissions of greenhouse gasses. In addition to promoting sustainable forms of mobility, rational route planning is also important. It is, therefore, reasonable to prepare the timetable of activities, stressing the importance of limiting unnecessary routes. In this paper, we will see how sustainable mobility can be addressed in a higher academic environment. Several proposals are presented to optimize mobility by rationalizing the organization of students' obligations within the faculty.
Keywords: sustainable mobility; timetable; air pollution; greenhouse gases; carbon footprint